Using a Radial, Switchable, Sector Ground Screen to Produce Azimuthal Directivity for a Monopole Antenna - Edmund K. Miller , (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Ground-mounted monopole antennas are usually driven against a radial-wire ground system to control their input impedance and to improve their radiation efficiency. This results in a radiation pattern that is uniform in azimuth angle with a front-to-back ratio of 1, or 0 dB. The use of a sectorial ground screen, one whose radial or angular extent is varied to produce a radiation pattern having azimuthal directivity has received some attention. An alternate approach also is explored in this discussion. It involves exploring the effect of varying the number of “active” radials in an otherwise uniform ground system of radial wires, an active radial being one that is electrically connected to the base of the monopole. A “passive” radial on the other hand is one that is separated from the monopole by a switch. By varying the number and angular locations of the active and passive ground wires, the resulting azimuth pattern can be varied in angle and directive gain. This arrangement makes possible a steerable pattern, something not usually associated with ground-mounted monopoles. The antenna and ground screen are modeled using the well-known NEC package. For convenience in modeling, active radials are made into passive ones by adding a large resistance between the base of the monopole and a given radial. Directive gains of more than 5 dB are found to be possible.